A UPLC-MS/MS application for comparisons of the hepatotoxicity of raw and processed Xanthii Fructus by energy metabolites. Issue 5 (21st January 2019) - Jiang, Hai; Yang, Liu; Xing, Xudong; Yan, Meiling; Guo, Xinyue; Hou, Ajiao; Man, Wenjing; Yang, Bingyou; Wang, Qiuhong; Kuang, Haixue
Abstract : The ripe fruit of Xanthium strumarium  L. (Xanthii Fructus) cannot be widely used as a Chinese herbal medicine (CHM) owing to its hepatotoxicity. Abstract : The ripe fruit of Xanthium strumarium L. (Xanthii Fructus) cannot be widely used as a Chinese herbal medicine (CHM) owing to its hepatotoxicity. However, Xanthii Fructus (XF) can be used effectively and safely after correct processing based on traditional experience, although a high hepatotoxicity risk remains owing to improper usage. Therefore, the processing methods used must be clarified to ensure safety. The adenosine-5′-triphosphate (ATP) level in tissues is an important indicator reflecting the functional status of liver cells. Therefore, this study aims to evaluate the hepatotoxicity of XF using UPLC-MS/MS. The hepatotoxicity of raw XF (RXF) and XF processed by intermediary energy metabolites (PXF) is compared. The method is evaluated for its analytical performance and successfully applied to the quantification of ATP, adenosine-5′-diphosphate (ADP), adenosine-5′-monophosphate (AMP), atractyloside, and carboxyatractyloside in mouse liver. The hepatotoxicity results also indicate that the toxicity of XF is decreased after processing, perhaps due to the decrease in atractyloside and carboxyatractyloside contents. Importantly, the experimental evidence provides a rationale for the reduction in toxicity. These data show that mouse livers are damaged between the days 20 and 30 of RXF oral administration, and that the ATP level is decreased. Importantly, no significant difference is observed between the PXF treatment group and control group, while the RXF treatment group is significantly different. Therefore, processing can reduce the toxicity of XF.